2015
DOI: 10.1121/1.4916195
|View full text |Cite
|
Sign up to set email alerts
|

Identification of high-pass filtered male, female, and child vowels: The use of high-frequency cues

Abstract: Vowels are characteristically described according to low-frequency resonance characteristics, which are presumed to provide the requisite information for identification. Classically, the study of vowel perception has focused on the lowest formant frequencies, typically F1, F2, and F3. Lehiste and Peterson [Phonetica 4, 161-177 (1959)] investigated identification accuracy of naturally produced male vowels composed of various amounts of low- and high-frequency content. Results showed near-chance identification p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…In other words, some listeners were more adept at identifying speaker gender from the high-pass filtered vowel segments than others, despite being matched for hearing sensitivity. This degree of variability was also observed in a previous study examining vowel category judgments from highpass filtered male, female, and child vowels (Donai & Paschall, 2015). The normal-hearing listeners in Donai and Paschall's study showed substantial differences in their abilities to identify vowel category from naturally produced, highpass filtered /hVd/ tokens from two adult male, two adult female, and two child speakers.…”
Section: Discussionsupporting
confidence: 78%
“…In other words, some listeners were more adept at identifying speaker gender from the high-pass filtered vowel segments than others, despite being matched for hearing sensitivity. This degree of variability was also observed in a previous study examining vowel category judgments from highpass filtered male, female, and child vowels (Donai & Paschall, 2015). The normal-hearing listeners in Donai and Paschall's study showed substantial differences in their abilities to identify vowel category from naturally produced, highpass filtered /hVd/ tokens from two adult male, two adult female, and two child speakers.…”
Section: Discussionsupporting
confidence: 78%
“…Vowels were recorded from two males, two females, and two children (one male and one female, both age 10) at 96 kHz and 24-bit resolution in an h/Vowel/d (hVd) context using a high fidelity microphone (Lawson 251) as described in Donai and Paschall. 3 Stimuli for the experiment consisted of five productions of six naturally produced, high-pass filtered hVd signals; /æ/ as in had, /i/ as in heed, /u/ as in who’d, /Ɔ/ as in hawd, //?// as in herd, and /e/ as in hayed . The hVd signals were recorded in connected speech using the carrier phrase, I say (hVd) again.…”
Section: Methodsmentioning
confidence: 99%
“…It was of interest to determine the effect, if any, sampling frequency had on classification accuracy, using a more traditional sampling frequency (48 kHz) and a less-commonly used, and higher, sampling frequency (96 kHz) used in Donai and Paschall. 3 For the second set, a 100 ms central portion of the vowel at a 48 kHz sample rate was used. To compute 13 dimensional MFCCs, window length and step time were set to 20 ms and 3 ms, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations